Mastering software quality assurance : best practices, tools and techniques for software developers - Chemuturi, Murali, 1950- (J. Ross Pub., 2011)
This is an essential guide to best practices for anyone involved in software development. Packed with expert advice and practical guidance, "Mastering Software Quality Assurance" is comprehensive guide to the four dimensions of software development quality - specifications, design, construction, and conformance - from both micro and macro viewpoints. From the micro view, it details aspects of building-in quality at component level to ensure ingrained quality. From the macro view, it addresses the organizational level activities that provide and environment conducive to fostering quality. This volume also explores a process driven approach to quality, and provides readers with the information, guidance, and confidence necessary to implement a process quality model